Makanan Tradisional Berbahan Tepung Terigu di Purwokerto - Tutik Handayani; Haryadi Haryadi (agriTECH, 2001)
There were traditional foods found in Purwokerto comprising 28 types made from 100% wheat flour as the main ingredient and 15 types made from composite flour. Wheat flour was used for all portion od the foods and for coating as well. Many traditional foods were most probably prepared based on the modification of Oriental and European recipes. Traditional foods which had been formerly made from rice flour were found to be prepared using wheat flour to substitute at various proportions. Higher proportion of wheat flour used in rice flour based food preparation decreased in hardness, but increased in elasticity and cohesiveness of the foods. Addition of tapioca starch to wheaten dough in traditional food making decreased in hardness but increased in cohesiveness of the processed food.